Abnormally Invasive Placenta—Prevalence, Risk Factors and Antenatal Suspicion: Results From a Large Population-based Pregnancy Cohort Study in the Nordic Countries. Issue 2 (June 2017) - Thurn, L.; Lindqvist, P.G.; Jakobsson, M.; Colmorn, L.B.; Klungsoyr, K.; Bjarnadóttir, R.I.; Tapper, A.M.; Børdahl, P.E.; Gottvall, K.; Petersen, K.B.; Krebs, L.; Gissler, M.; et al.
Abstract : ( BJOG . 2016;123:1348–1355) An abnormally invasive placenta (AIP), caused by abnormal invasion of the chorionic villi into the myometrium, presents a significant risk of hemorrhage, peripartum hysterectomy, and other complications. It has been reported to occur in 2 to 90 per 10, 000 births. Risk factors include placenta previa, prior cesarean section (CS) especially in combination with placenta previa, and increasing maternal age and parity. Fewer complications have been observed when a planned operative delivery is undertaken in patients with AIP. Therefore, antenatal suspicion of AIP is important in the management of these patients. This study aimed to assess prevalence, risk factors, risk groups and antenatal suspicion of AIP as part of the Nordic Obstetric Surveillance Study.